Advances in seismic imaging of magma and crystal mush - Paulatto, Michele; Hooft, Emilie E. E.; Chrapkiewicz, Kajetan; Heath, Benjamin; Toomey, Douglas R.; Morgan, Joanna V. (Frontiers in Earth Science, 2022)
Seismic imaging methods have provided detailed three-dimensional constraints on the physical properties of magmatic systems leading to invaluable insight into the storage, differentiation and dynamics of magma. These constraints have been crucial to the development of our modern understanding of magmatic systems. However, there are still outstanding knowledge gaps resulting from the challenges inherent in seismic imaging of magmatic systems. These challenges stem from the complex physics of wave propagation across highly heterogeneous low-velocity anomalies associated with magma reservoirs. Ray-based seismic imaging methods such as travel-time and surface-wave tomography lead to under-recovery of such velocity anomalies and to under-estimation of melt fractions. This review aims to help the volcanologist to fully utilize the insights gained from seismic imaging and account for the resolution limits. We summarize the advantages and limitations of the most common imaging methods and propose best practices for their implementation and the quantitative interpretation of low-velocity anomalies. We constructed and analysed a database of 277 seismic imaging studies at 78 arc, hotspot and continental rift volcanoes. Each study is accompanied by information about the seismic source, part of the wavefield used, imaging method, any detected low-velocity zones, and estimated melt fraction. 39 studies attempted to estimate melt fractions at 22 different volcanoes. Only five studies have found evidence of melt storage at melt fractions above the critical porosity that separates crystal mush from mobile magma. The median reported melt fraction is 13% suggesting that magma storage is dominated by low-melt fraction crystal mush. However, due to the limits of seismic resolution, the seismological evidence does not rule out the presence of small (< 10 km3) and medium-sized (< 100 km3) high-melt fraction magma chambers at many of the studied volcanoes. The combination of multiple tomographic imaging methods and the wider adoption of methods that use more of the seismic wavefield than the first arriving travel-times, promise to overcome some of the limitations of seismic tomography and provide more reliable constraints on melt fractions. Wider adoption of these new methods and advances in data collection are needed to enable a revolution in imaging magma reservoirs.